Rekayasa Media Pembelajaran Berbasis Web untuk Pelajaran Matematika Kelas V - Widayanti, Devi; , Hernawan Sulistyanto, S.T., M.T (2016)
The Educators are required to utilize computer technology in teaching material to students with learning media is interesting, conceptual and qualified to meet the minimum completeness kiriteria value (KKM). The one of them is a math lesson in learning the measurement of time, distance and speed. The method used is using a qualitative approach and action research methods class. Thus the creation of a media-based mathematics learning website using HTML, PHP and Javascript. This research it is known that the suitability of the image with the subject matter presented to help students understand the lesson, it is marked by 20 students from 26 students state that images on the website created to support the material measurement of time, distance, and speed. And the exercises increased 27% from 58% before testing after testing with 85% of students know or understand the material presented in the test.